SURVEY RESULTS OF MANUFACTURER PRICE IN THE BANK INDONESIA LHOKSEUMAWE MONTH OF SEPTEMBER 2022 - Muammar Khaddafi; Mohd Heikal; Chalirafi; Munandar; Rico Nur Ilham (RADJA PUBLIKA, 2022)
The goal to be achieved in this research is to support Bank Indonesia (BI) in updating the data of the Information Center for Strategic Food Prices (PIHPS), which is an information center containing the prices of 10 strategic food commodities aimed at monitoring prices, coordinating policies and means to expand access to information. for society. The methods used in this research are community empowerment methods, program implementation methods and activity roadmaps that target producers, namely companies/industry/farmer households/agricultural group associations that produce goods. In general, the methodology for enumeration of price data is carried out by direct interviews every month with respondents.